Does ureteral stenting matter for stone size? A retrospective analyses of 1361 extracorporeal shock wave lithotripsy patients - Ozkan, Burak; Dogan, Cagatay; Can, Gulce Ecem; Tansu, Nejat; Erozenci, Ahmet; Onal, Bulent (POLISH UROLOGICAL ASSOC, 2015)
Introduction The aim of our study was to determine the efficacy of ureteral stents for extracorporeal shock wave lithotripsy (SWL) treatment of pelvis renalis stones and to compare the results and complications in stented and non-stented patients. Material and methods Between 1995 and 2011, 1361 patients with pelvis renalis stones were treated with SWL. Patients were subdivided into three groups according to stone burden: <= 1 cm(2) (group 1

n = 514), 1.1 to 2 cm(2) (group 2

n = 530) and >2 cm(2) (group 3

n = 317). Each group was divided into subgroups of patients who did and did not undergo ureteral stent implantation before SWL treatment. The efficacy of treatment was evaluated by determining the effectiveness quotient (EQ). Statistical analysis was performed by chi-square, Fisher's exact and Mann-Whitney U tests. Results Of the 514, 530 and 317 patients in groups 1, 2 and 3 respectively, 30 (6\%), 44 (8\%) and 104 (33\%) patients underwent auxiliary stent implantation. Steinstrasse rates did not differ significantly between stented and non-stented patients in each group. The EQ was calculated as 62\%, 33\% and 70\% respectively in non-stented, stented and totally for group 1. This ratio calculated as 58\%, 25\% and 63\% for group 2 and 62\%, 26\% and 47\% for group 3. Stone-free rates were significantly higher for non-stented than for stented patients in groups 2 and 3. Conclusions Stone free rates are significantly higher in non-stented than in stented patients with pelvis renalis stones >1 cm(2), whereas steinstrasse rates are not affected.
Keywords: pelvis renalis stone; stent; SWL; stone size